PENGARUH PENGGUNAAN POLLARD DAN ASAM AMINO SINTETIS DALAM PAKAN AYAM PETELUR TERHADAP KONSUMSI PAKAN, KONVERSI PAKAN, DAN PRODUKSI TELUR - Nonok Supartini (BUANA SAINS, 2006)
This objective of the experiment was to measure the effect of pollard utilization on the layer diets and the addition of critical amino acid to produce the consumption, eggs production and feed conversion with layers. The experiment used 315 Lohmann strains that comprising 7 treatments in 7 replications with 15 birds each. The treatments were: RO (control diet without pollard and without critical of AA), R1 (10% pollard + 50% critical of AA), R2 (10% pollard + 100% critical of AA), R3 (20% pollard + 50% critical of AA), R4 (20% pollard + 50% critical of AA), R5 (30% pollard + 50% critical of AA), R6 (30% pollard + 100% critical of AA). The results showed that the utilization of pollard with amino acid addition gave no significant different on consumption, egg production (%HAD) and feed conversion with layers